The Role of Spiritual and Moral Education in the Stability of the Family Environment - Davronova Dildora Saidovna (Genius Journals, 2022)
This article talks about the importance of the family, the stability of the family environment and the role of spiritual and moral education in it. In addition, this article discusses the priority tasks that should be paid attention to in the development of children's education today
Keywords: Family; manners; education; environment